Gut microbiota variation between climatic zones and due to migration strategy in passerine birds - Schmiedová, Lucie; Kreisinger, Jakub; Kubovčiak, Jan; Těšický, Martin; Martin, Jean-Francois; Tomášek, Oldřich; Kauzálová, Tereza; Sedláček, Ondřej; Albrecht, Tomáš (Frontiers in Microbiology, 2023)
Decreasing biotic diversity with increasing latitude is an almost universal macroecological pattern documented for a broad range of taxa, however, there have been few studies focused on changes in gut microbiota (GM) across climatic zones. Using 16S rRNA amplicon profiling, we analysed GM variation between temperate (Czech Republic) and tropical (Cameroon) populations of 99 passerine bird species and assessed GM similarity of temperate species migrating to tropical regions with that of residents/short-distance migrants and tropical residents. Our study also considered the possible influence of diet on GM. We observed no consistent GM diversity differences between tropical and temperate species. In the tropics, GM composition varied substantially between dry and rainy seasons and only a few taxa exhibited consistent differential abundance between tropical and temperate zones, irrespective of migration behaviour and seasonal GM changes. During the breeding season, trans-Saharan migrant GM diverged little from species not overwintering in the tropics and did not show higher similarity to tropical passerines than temperate residents/short-distance migrants. Interestingly, GM of two temperate-breeding trans-Saharan migrants sampled in the tropical zone matched that of tropical residents and converged with other temperate species during the breeding season. Diet had a slight effect on GM composition of tropical species, but no effect on GM of temperate hosts. Consequently, our results demonstrate extensive passerine GM plasticity, the dominant role of environmental factors in its composition and limited effect of diet.